Plantas herbáceas : perspectivas para mitigação de impactos antrópicos no entorno de trilhas em áreas protegidas - Silva, Anderson Moraes da (2022)
Protected areas are essential for the conservation of biodiversity. In protected areas with public visitation, the trails are an opportunity for greater contact with nature and appreciation of natural resources. However, negative impacts are caused by the use of trails. Among the main impacts is soil compaction, increased surface water runoff and, consequently, erosion. At the university, a project to extend visitation on trails also detected impacts that required research solutions to minimize them. Protected areas are rich in herbaceous species with the potential to contribute to the mitigation of human impacts around trails. However, studies that show this sustainable management strategy and indicate such species with potential for use in these actions are still lacking. In this sense, the present study sought to identify herbaceous species with potential for use in actions to reduce anthropic impacts around trails in protected areas, test the potential for propagation and ex situ survival of the species and evaluate the response of the chosen plants regarding the factors substrate compaction and water restriction. Field expeditions were carried out and the species Tradescantia fluminensis and Calyptocarpus brasiliensis were selected, which stood out for their homogeneous soil cover and presence in places with different conditions of humidity and luminosity. In the experiments carried out with these species, the combination of substrate compaction and water restriction factors were the treatments. The response variables were the shoot dry mass, the substrate coverage by the shoots of the plants and the root growth. The species were evaluated under winter and summer conditions. Both species showed excellent percentages of survival and ex situ propagation, both in the experiment carried out in summer and in the experiment carried out in winter. We conclude that T. fluminensis and C. brasiliensis have the potential to contribute to the mitigation of anthropic impacts in the surroundings of trails, which can alleviate soil compaction and erosion.